Motor Axonal Regeneration after Partial and Complete Spinal Cord Transection - Lu, Paul (Society for Neuroscience, 2012)
We subjected rats to either partial midcervical or complete upper thoracic spinal cord transections and examined whether combinatorial treatments support motor axonal regeneration into and beyond the lesion. Subjects received cAMP injections into brainstem reticular motor neurons to stimulate their endogenous growth state, bone marrow stromal cell grafts in lesion sites to provide permissive matrices for axonal growth, and brain-derived neurotrophic factor gradients beyond the lesion to stimulate distal growth of motor axons. Findings were compared with several control groups. Combinatorial treatment generated motor axon regeneration beyond both C5 hemisection and T3 complete transection sites. Yet despite formation of synapses with neurons below the lesion, motor outcomes worsened after partial cervical lesions and spasticity worsened after complete transection. These findings highlight the complexity of spinal cord repair and the need for additional control and shaping of axonal regeneration.